Evaluasi User Interface, Efficiency, dan Accessibility dalam Meningkatkan Usability dan User Satisfaction Aplikasi M-Paspor - Ahmad Jidan Abrar; Usep Suhud; Meta Bara Berutu (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of Efficiency, Accessibility, and User Interface on User Satisfaction and Usability in the context of interactive digital systems. A quantitative approach was applied using the Structural Equation Modeling (SEM) method supported by AMOS software. Data were collected through an online survey distributed to respondents who met the inclusion criteria, and were subsequently analyzed through Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) to ensure construct validity and instrument reliability. Hypothesis testing was conducted on verified latent constructs to examine causal relationships between variables. The results indicate that Accessibility and User Interface have a significant impact on User Satisfaction and Usability, while Efficiency was found to have no significant influence. These findings contribute to the theoretical framework in the field of Human–Computer Interaction (HCI) and offer practical recommendations for system developers to enhance the overall quality of digital user experiences.